Spatial and temporal monitoring of drought hazards in Opak Watershed - Suhardono Sapta; Septiariva Iva Yenis; Wijayanti Sovia; Ibriza Naila Maulida; Suryawan I Wayan Koko (E3S Web of Conferences)
The Opak Watershed in Yogyakarta Province has been under persistent drought threat. This study monitored drought conditions spatially and temporally using Sentinel-2 satellite imagery and rainfall data. The Standardized Precipitation Index (SPI) was employed for drought assessment based on rainfall, while the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Moisture Index (NDMI) evaluated drought via satellite images. A Pearson correlation analysis revealed significant relationships: SPI and NDVI (r = 0.527), SPI and NDMI (r = 0.704), and NDVI and NDMI (r = 0.921). The findings provide a comprehensive understanding of drought patterns and trends, revealing critical insights into the development of drought conditions over time and across various locations within the Opak Watershed.